(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The gender-related controversies associated with effects of various teaching methods gave rise to this study. This study was conducted to ascertain the gender-relative effect of project-based learning method on academic achievement and retention of technical college students in Basic Electricity. The study was carried out in Anambra state and adopted the quasi-experimental research design. This was precisely, pretest, posttest, delayed posttest non-randomized control group design which involved groups of students in their intact classes. A sample of 92 NTC II students was drawn from a population of 179 students of state owned technical colleges in Anambra state. Two research questions and two null hypotheses tested at 0.05 level of significance guided the study. Basic Electricity Achievement Test (BEAT), a 40-item multiple choice test which was based on the units covered in the study, served as the instrument used for data collection. The BEAT and lesson plans for both control and experimental groups were all validated by three experts from the faculty of education, Nnamdi Azikiwe University Awka. The reliability coefficient of the instrument was found to be 0.82 using KR-20. Mean and standard deviation were used to answer the research questions, while Analysis of Covariance (ANCOVA) was employed to test the hypotheses. Findings revealed that male and female technical college students taught Basic electricity using project-based learning method had higher achievement and retention scores than those taught using the conventional teaching method. Also findings revealed that there was no significant difference in the mean achievement and retention scores of the male and female students taught basic electricity using PBLM. Based on the findings of this study, it was concluded that PBLM has the potential to improve male and female technical college students’ academic achievement and retention in Basic electricity. Consequently, it was recommended among others that Basic electricity teachers should use PBLM in the teaching of Basic electricity and grant students equal opportunity during classroom instructions irrespective of gender so as to enhance students’ academic achievement and retention in the subject.